Spatial Constancy of Surface-Embedded Layouts across Multiple Environments - Ens, Barrett; Ofek, Eyal; Bruce, Neil; Irani, Pourang (ACM - Association for Computing Machinery, 2015)
We introduce a layout manager that exploits the robust sensing capabilities of next-generation head-worn displays by embedding virtual application windows in the user’s surroundings. With the aim of allowing users to find applications quickly, our approach leverages spatial memory of a known body-centric configuration. The layout manager balances multiple constraints to keep layouts consistent across environments while observing geometric and visual features specific to each locale. We compare various constraint weighting schemas and discuss outcomes of this approach applied to models of two test environments.